Chris Lorenz's idea of conceptual inversion - Domanska, Ewa (Historein, 2013)
The text deals with Chris Lorenz’s idea of conceptual inversion, understood as an epistemological blockade that stands as a barrier to the development of a proper theory of humanities and social sciences. According to Lorenz, the methodological and theoretical views of scientific programmes embody negations (i.e. inversions) of the views being criticized by them. Because of this process of “turning upside down”, many of the conceptual problems connected with the criticized positions survive. The author asks two questions: first, about the relation between Lorenz’s idea of conceptual inversion and Imre Lakatos’ idea of reconfigurations of research programmes, and, second, about possible common ground on which Lorenz’s interest in empiricism emerging out of his criticism of narrativism, and Ewa Domanska’s interest in new empiricism related to posthumanism (also critical of textual constructivism), could meet.